The Martian atmospheric ion escape rate dependence on solar wind and solar EUV conditions: 1. Seven years of Mars Express observations. Issue 7 (29th July 2015) - Ramstad, Robin; Barabash, Stas; Futaana, Yoshifumi; Nilsson, Hans; Wang, Xiao‐Dong; Holmström, Mats
Abstract More than 7 years of ion flux measurements in the energy range 10 eV–15 keV have allowed the ASPERA‐3/IMA (Analyzer of Space Plasmas and Energetic Ions/Ion Mass Analyzer) instrument on Mars Express to collect a large database of ion measurements in the Mars environment, over a wide range of upstream solar wind (density and velocity) and radiation (solar EUV intensity) conditions. We investigate the influence of these parameters on the Martian atmospheric ion escape rate by integrating IMA heavy ion flux measurements taken in the Martian tail at similar (binned) solar wind density (nsw), velocity (vsw), and solar EUV intensity (IEUV) conditions. For the same solar wind velocity and EUV intensity ranges (vsw and Is constrained), we find a statistically significant decrease of up to a factor of 3 in the atmospheric ion escape rate with increased average solar wind density (5.6 × 1024s−1 to 1.9 × 1024s−1 for 0.4 cm−3 and 1.4 cm−3, respectively). For low solar wind density (0.1–0.5 cm−3) and low EUV intensity, the escape rate increases with increasing solar wind velocity from 2.4 × 1024s−1 to 5.6 × 1024s−1. During high solar EUV intensities the escape fluxes are highly variable, leading to large uncertainties in the estimated escape rates; however, a statistically significant increase in the escape rate is found between low/high EUV for similar solar wind conditions. Empirical‐analytical models for atmospheric escape are developed by fitting calculated escape rates to all sufficiently sampled upstream conditions.